Compression after Impact: Damage Characterization of Multi-Directional 10-Ply Carbon- Epoxy Prepreg Laminates Subject to Quasi-Static Impact Force - Lo Ricco, Marco; El-Hajjar, Rani (Proceedings of the Wisconsin Space Conference, 2011)
During the course of service, aerospace structures inevitably will suffer some form of damage, including the possibility of impact. Two general types of impact damage, either resulting from a quasi-static force or a dynamic impulse force, characterize the nature of impact threats for analysis and experimentation in a lab setting. Using ASTM D7137 Standard Test method for Compressive Residual Strength Properties of Damaged Polymer Matrix Composite, this study subjects multidirectional carbon-fiber/epoxy laminates to Compression After Impact (CAI) tests to determine whether the results may be used to characterize and quantify the effects of impact damage on laminate compressive strength. Characterization of impact damage in regions of a structure subject to high-strain compression could assist decision-making in implementing repairs. In addition, this paper examines the effects of different impacting patterns on the behavior in compression.Â 